Individual particle morphology, coatings, and impurities of black carbon aerosols in Antarctic ice and tropical rainfall. Issue 22 (19th November 2016) - Ellis, Aja; Edwards, Ross; Saunders, Martin; Chakrabarty, Rajan K.; Subramanian, R.; Timms, Nicholas E.; van Riessen, Arie; Smith, Andrew M.; Lambrinidis, Dionisia; Nunes, Laurie J.; Vallelonga, Paul; Goodwin, Ian D.; et al.
Abstract: Black carbon (BC) aerosols are a large source of climate warming, impact atmospheric chemistry, and are implicated in large‐scale changes in atmospheric circulation. Inventories of BC emissions suggest significant changes in the global BC aerosol distribution due to human activity. However, little is known regarding BC's atmospheric distribution or aged particle characteristics before the twentieth century. Here we investigate the prevalence and structural properties of BC particles in Antarctic ice cores from 1759, 1838, and 1930 Common Era (C.E.) using transmission electron microscopy and energy‐dispersive X‐ray spectroscopy. The study revealed an unexpected diversity in particle morphology, insoluble coatings, and association with metals. In addition to conventionally occurring BC aggregates, we observed single BC monomers, complex aggregates with internally, and externally mixed metal and mineral impurities, tar balls, and organonitrogen coatings. The results of the study show BC particles in the remote Antarctic atmosphere exhibit complexity that is unaccounted for in atmospheric models of BC. Key Points: Individual black carbon particles extracted from Antarctic ice Single spherule black carbon aerosol particles found in modern rain and in ice cores dating both before and after industrialization Black carbon particles found with iron inclusions, suggesting a transport pathway for iron deposition in the Southern Ocean